Deformations and ruptures in human lenses with cortical cataract subjected to ex vivo simulated accommodation - Michael, R; D'Antin, JC; Pinilla Cortés, L; Burd, HJ; Sheil, B; Barraquer, RI (Association for Research in Vision and Ophthalmology, 2021)
Purpose: Human cortical opacities are most commonly accompanied by changes in lens fiber structure in the equatorial region at the lens nucleus–cortex interface. Cortex and nucleus have different elastic properties, which change with age. We therefore subjected ex vivo lenses to simulated accommodation and studied the internal deformations to better understand the mechanism of cortical cataract formation. Methods: Nine human donor lenses (33–88 years old) were tested using a bespoke radial stretching device for anterior eye segments. Seven of the lenses exhibited cortical cataracts. The other two lenses, without cataract, were used as controls. Frontal and cross-sectional images of the lens obtained during stretching facilitated measurements on equatorial lens diameter and central lens thickness in the stretched and unstretched states. Results: Stretching caused the lens equatorial diameter to increase in all cases. Conversely, the lens central thickness showed no systematic variation during stretching. For four of the lenses with cortical cataract, ruptures were observed during stretching at the nucleus–cortex boundary adjacent to the cortical cataracts. Ruptures were not observed in the control lenses or in the three other lenses with cortical cataract. Conclusions: Internal ruptures can occur in aged ex vivo lenses subjected to simulated disaccommodation. These ruptures occur at the nucleus–cortex interface; at this location, a significant stiffness discontinuity is expected to develop with age. It is hypothesized that ruptures occur in in vivo lenses during accommodation—or attempted accommodation.